Emerging connections between oxidative stress, defective proteolysis, and metabolic diseases. (1st December 2020) - Homma, Takujiro; Fujii, Junichi
Abstract: The ubiquitin–proteasome system (UPS) and autophagy are two major intracellular proteolytic systems that are closely associated with each other. Because UPS and autophagy are involved in the clearance of oxidised and/or aggregated proteins, it would be logical to assume that alterations in proteolysis would accompany pathological conditions. Indeed, both systems are themselves susceptible to oxidative modification and therefore could be a prominent target of reactive oxygen species (ROS). Oxidative stress appears to be a common underlying factor in the development of and the pathogenesis of various metabolic diseases, including non-alcoholic fatty liver disease (NAFLD) and type 2 diabetes (T2D). Recent studies, using obesity and hyperglycaemia model mice, reported that both UPS and autophagy systems are inhibited in these mice and that this inhibition is accompanied by lipid accumulation, insulin resistance, and tissue damage. However, the detailed molecular mechanisms that are responsible for regulating intracellular proteolysis in metabolic diseases are not well understood. In the current review, we discuss the correlation between oxidative stress, defective proteolysis, and metabolic diseases. An understanding of how ROS affects intracellular proteolysis may provide new perspectives on the development of and control of diseases.